2021
DOI: 10.1371/journal.pone.0260427
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of dental caries among adolescent patients attending Hospitals in West Wollega Zone, Western Ethiopia: A case-control study

Abstract: Background Dental caries is a prevalent disease in both developed and developing countries and is a public health problem among adolescents. This study aimed to assess the determinants of dental caries among adolescent patients in the west Wollega Zone, Western Ethiopia. Methods A hospital-based unmatched case-control study design was conducted in West Wollega Zone, West Ethiopia. A total of 133 cases and 266 controls participated in this study. Data were collected using pre-tested questionnaires from three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Furthermore, those who had khat chewing habits were found significantly associated with tooth decay. The study in Butajira town and the West Wollega zone in Ethiopia supports this finding (46,51). On the other hand, this finding is in contrast to a study reported in Jimma, Ethiopia (26).…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, those who had khat chewing habits were found significantly associated with tooth decay. The study in Butajira town and the West Wollega zone in Ethiopia supports this finding (46,51). On the other hand, this finding is in contrast to a study reported in Jimma, Ethiopia (26).…”
Section: Discussionsupporting
confidence: 63%
“…Recently, in recognition of the multifaceted burden of oral diseases worldwide, the urgency of understanding social determinants of poor oral health was underscored in the 74 th World Health Assembly in 2021 to redirect attention to the root causes of oral health disparities [ 5 ]. Despite the evidence that not all determinants of a health-disease process can be disclosed at an individual level, [ 6 ] to date, oral health research has focused primarily on exploring lifestyle factors such as dietary and oral hygiene practices involved in escalating the global burden of dental caries [ 7 , 8 ] while putting less emphasis on social structures that shape those risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence links qat chewing with many systemic and oral diseases. However, the evidence on the habit association with development of dental caries is conflicting, with many study supported this notion [ 18 , 19 , 25 – 27 ] while others didn’t [ 15 , 20 , 21 ]. In light of such a controversy, this study aimed to fill the gap.…”
Section: Discussionmentioning
confidence: 99%